Existence results for nonlinear boundary-value problems with integral boundary conditions in Banach spaces - Zhang, Xuemei; Feng, Meiqiang; Ge, Weigao (Nonlinear analysis, 2008)
This paper investigates the multiplicity of positive solutions for a class of nonlinear boundary-value problems of fourth-order differential equations with integral boundary conditions in ordered Banach spaces. The arguments are based upon a specially constructed cone and the fixed point index theory in cone for strict set contraction operator. The nonexistence of positive solution is also studied. Meanwhile, an example is worked out to demonstrate the main results.